The new competitive landscape - Bettis, Richard A.; Hitt, Michael A. (Strategic Management Journal, 1995)
Technology is rapidly altering the nature of competition and strategy in the late twentieth century, moving us toward a ‘new competitive landscape’ in the twenty-first century. The new competitive landscape presents new issues, new concepts, new problems and new challenges. This essay examines the broad nature of the technological changes that are occurring and identifies some of the important implications of these changes for strategic management. The purpose of the paper is to stimulate further research into these issues in strategic management and to provide an overall context for the other papers appearing in this special issue.